Association between Vitamin D deficiency and Risk of Heart Failure-A Clinical Case Control Study - Dr. Shaker Kadhium Taher (Academic Journal of Clinicians, 2024)
Background: Heart failure (HF) is a complex clinical syndrome represents a serious public health problem globally. Vitamin D deficiency is highly frequent among Iraqi population. Vitamin D deficiency appears as an emerging risk factor of heart failure. Objective: To assess the association between vitamin d deficiency and risk of heart failure. Method: This was a case control study conducted during the period January, 2023 to of April 2024 in Al Samawa City. Included 52 Iraqi patients with proved diagnosed heart failure and almost matched 52 healthy individuals as control group. Both cases and controls aged 40 - 70 years. Results: The mean age of 53.5 ± 8.2 years in HF group and 52.9 ± 10.1 in controls’ group. Females were relatively dominant in both group, contributed for 51.9% and 53.8%, respectively. In all demographic variables, no significant differences were found (P. value > 0.05). Comparison of mean value of 25(OH)D of HF patients and controls revealed a highly significant lower levels in HF group compared to controls where the mean 25(OH)D was 9.63 ± 4.92 ng/mL and 16.22 ± 7.11 ng/mL, respectively, (P. value<0.001). among HF group, 46 patients (88.5%) had vitamin D (VD) deficiency (25(OH)D <20 ng/mL), 5 (9.6%) patients had insufficient VD (25(OH)D : 20 - <30 ng/mL) and only one patient (1.9%) had sufficient level of VD (25(OH)D ≥ 30 ng/mL). the mean 25 (OH) D was 8.1 ± 2.8 ng/mL in patients with HFrEF (EF≤ 40%) and it was significantly lower than that of patients with HFmEF and those with HFpEF, 9.8 ± 3.1 and 13.5 ± 4.1 ng/mL, respectively, (P. value < 0.001). Conclusions: Vitamin D deficiency appeared to a significant independent risk factor of heart failure among Iraqi patients. Older age , female gender and low 25(OH)D < 20 ng/mL were significant predictors of Heart failure. We recommended conducting further studies for more precise conclusions.